Stakeholders Theory and Its effects on Organization's Technological Change - Maryam Abdalrazaq Alsbaity; Majdi Anwar Quttainah (Journal of International Conference Proceedings (JICP), 2018)
This paper intends to investigate the effectiveness of the Stakeholders Theory in the organizational process of Technological change. It focuses on the importance of involving every stakeholder in the decision-making process. This focal point will be interpreted through integrating the Systems Theory with the organization's adaptive stage. It also shows how the Board of Directors (hereinafter, BODs)1and the executives manage this change and apply leadership skills when dealing with each stakeholder. This research deploys the stakeholders’ theory specifically focusing on shareholders, investors, management, employees and customers.The anticipated findings indicatethat the application of governance theories and specially stakeholders’ theory is highly impactful. This paper intends to compare the typical outcomes based on literature with outcomes based on real life applications of organizational technological change. It shall be interpretedthrough aselection of change management models, CVC2 analysis and technological change models.Moreover, measurements of the outcomes for eachstakeholder's participation will be presented through (e.g. employees performance, ROI3, etc.). Keywords: Organizations, Technology, Organizational change, Stakeholders Theory, Stakeholders.